Understanding and Predicting Job Losses Due to COVID-19 : Empirical Evidence from Middle Income Countries - Hatayama, Maho; Li, Yiruo; Osborne, Theresa (World Bank, Washington, DC, 2022)
This paper utilizes firm survey data to understand which formal private sector jobs are most at risk from COVID-19 or similar future crises, based on empirical evidence from two middle income economies. In particular, it estimates the importance for formal private-sector job losses of various COVID-19 pandemic-related labor market shocks and mitigating factors, such as the closure of non-essential industries, workers’ ability to perform their jobs from home, infection risks to workers, customers’ infection risk, global demand shocks, input supply constraints, employers’ financial constraints, and government support, in determining the level and distribution of job losses. This provides an empirical identification of the main risk factors for job loss and a basis for predicting the level and distribution of these losses due to the crisis. The methodology is applied to permanent formal private sector (PFPS) jobs in core productive manufacturing and services sectors (captured by World bank Enterprise Surveys) in Jordan and Georgia, which contain the requisite data to link occupational structure, task content, and firm-level shocks. Comparing empirical findings across the two, the paper assesses the degree of commonality of these risk factors. Job losses are projected for different groups within the employed population prior to the outbreak of COVID-19 and compared with post-crisis labor force data. The results indicate that in these countries the level of job losses is predominantly due to a reduction in demand rather than a reduction in the supply of labor. Closures, global demand shocks, supply disruptions, and other unexplained demand side shocks are significant determinants of jobs lost. Sensitivity of employment to closures, supply disruptions, and sales shocks was of similar magnitude in both countries; however, variation in infection risk was a significant determinant of sales only in Georgia. At the same time, Georgian formal firms were better able to rebound their sales and hire back workers than formal firms in Jordan. Finally, the paper finds no evidence that firms with workers performing tasks that can be performed from home were better able to preserve jobs, given the dominant role of firm-level demand and supply chain shocks.